Pengaruh Edukasi Akhir dengan Video Diet Terhadap Pengetahuan dan Keterampilan Pasien DM Tipe II di RSUD Sultan Imanuddin Pangkalan Bun: The Effect of Final Educatione with Video Diet on Knowledge and Skill of Type II DM Patients at RSUD Sultan Imanuddin Pangkalan Bun - Fretika Utami Dewi; Maria Maria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Knowledge in managing diabetes mellitus is very important because it can affect the way of life of patients in managing their disease. One of the means to improve patient knowledge and skills is to use video as a source of information about the diabetes mellitus diet (3 J). This study aims to determine the effect of final education with diet videos on knowledge and skills before and after education in type II DM patients. The research design uses a Quasy Experimental Design with a Pre Post Test Only One Group Design research design. The sampling technique was purposive sampling with a total of 18 samples. Inclusion criteria: aged 30-59 years, owning a smartphone, with or without complications of obesity, hypertension, dyslipidemia and complications of kidney, cancer, liver as exclusion criteria. Data was collected using a knowledge and skills questionnaire that has been tested for validity and reliability. Data analysis was carried out using univariate and bivariate (paired t test and Wilcoxon test). The results showed that the age of the sample was between 31-59 years and the most sex was female 66.67%, with the highest education level being high school/equivalent, namely 55.56%, long suffering from DM > 5 years was 61.11%, had a history of DM disease was 66.67%, the frequency of watching educational video diet ≥3 times was 61.11%, blood sugar levels after education decreased by 100%, knowledge increased by 77.78% and skills increased by 94.44%. The results of the analysis show the effect of final education with diet videos on the knowledge and skills of Type II DM patients before and after hospitalization at RSUD Sultan Imanuddin Pangkalan Bun.